2008
DOI: 10.1103/physrevb.77.094422
|View full text |Cite
|
Sign up to set email alerts
|

Chemical potential shift induced by double-exchange and polaronic effects inNd1xSrxMnO3

Abstract: We have studied the chemical potential shift as a function of temperature in Nd1−xSrxMnO3 (NSMO) by measurements of core-level photoemission spectra. For ferromagnetic samples (x = 0.4 and 0.45), we observed an unusually large upward chemical potential shift with decreasing temperature in the low-temperature region of the ferromagnetic metallic (FM) phase. This can be explained by the double-exchange (DE) mechanism if the eg band is split by dynamical/local Jahn-Teller effect. The shift was suppressed near the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Therefore, we attribute the upward shifts with increasing bandwidth to the double-exchange interaction with the Jahn-Tellersplit e g band as shown in Fig. 4(f), consistent with the temperature-dependent ∆µ [10].…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Therefore, we attribute the upward shifts with increasing bandwidth to the double-exchange interaction with the Jahn-Tellersplit e g band as shown in Fig. 4(f), consistent with the temperature-dependent ∆µ [10].…”
supporting
confidence: 81%
“…∆µ in LSMO, which has the widest bandwidth among the manganites, exhibited a monotonous shift without indication of chemical potential pinning, reflecting that there is no intrinsic stripe formation in LSMO [8,9]. As for the effect of double-exchange interaction on ∆µ, an upward ∆µ with decreasing temperature has been found in the low-temperature part of the ferromagnetic metallic (FM) phase and attributed the shift to the change of bandwidth under Jahn-Teller-split e g band induced by double-exchange interaction [10]. This observation is consistent with the theoretical prediction using oneorbital double-exchange model by Furukawa [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS results revealed that the binding energy of Ti 2p 3/2 (458.1 eV for La 0.75 K 0.25 SrMnTiO 6 and 458.0 eV for La 0.75 K 0.25 BaMnTiO 6 ) corresponds to that of previously reported Ti 4+ oxidation state 31 and the binding energy of Mn 2p 3/2 (642.3 eV for La 0.75 K 0.25 SrMnTiO 6 and 642.2 eV for La 0.75 K 0.25 BaMnTiO 6 ) is an intermediate value between those of Mn 3+ and Mn 4+ . 32 Therefore, the valence of Ti atoms is tetravalent, whereas that of the Mn atoms is a mixed Mn 3+ /Mn 4+ , which is consistent with the charge neutrality calculated for the title compounds. The XPS spectra of K 2p, La 3d, Sr 3d, Ba 3d, and O 1s qre given in Figure S1.…”
Section: Inorganic Chemistrysupporting
confidence: 86%
“…From the core level studies of CMR systems, there are many reports regarding the chemical potential shifts [20][21][22] as a function of concentraions at room temperature. But a few study has been reported at low * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%